The impact of BMI and smoking on risk of revision following knee and hip replacement surgery: evidence from routinely collected data - Burn, E; Edwards, CJ; Murray, DW; Silman, A; Cooper, C; Arden, NK; Prieto-Alhambra, D; Pinedo-Villanueva, R (Elsevier, 2019)
Objective The aim of this study was to assess the association of body mass index (BMI) and smoking with risk of revision following total knee replacement (TKR) and total hip replacement (THR).